Procesos biotecnológicos para la implantación e inducción de callos en Cinchona officinalis L., a partir de plántulas del invernadero, a nivel de laboratorio en la provincia de Loja. - Guartanza Loja, Jessica Alejandra (2019)
The Cascarilla, Cinchona officinalis L., it is a native species of the province of Loja, considered one of the most important genera for its medicinal, cultural and historical value, known as the National Tree of Ecuador (Anda, 2002); Between the 17th and 19th centuries, due to the over-exploitation and alteration of its ecosystem, the populations of C. officinalis L., were threatened, causing the species to disappear in many places in the province. Currently C. officinalis L., is in the category threatened by its high propagation difficulty “in vivo”, and the very low germination rate of its seeds, although isolated individuals can still be found in pastures, forming small wooded relics (Menesses, 2017). The Plant Micropropagation is a tool for the conservation of threatened species, by means of in vitro culture techniques the number of individuals can be increased per unit area of any species; as well as, it allows to conserve phytogenetic resources that present difficulties to propagate and stay in their natural environment. Under this perspective, the research was carried out with the purpose of contributing with protocols for the micropropagation of Cinchona officinalis L., in the stages of implantation and induction of explant calli from coded seedlings of the greenhouse, for the purpose of conservation and genetic improvement. The present research work was part of the macro project "Biotechnological processes to initiate the genetic improvement of Cinchona officinalis L., coming from forested relicts of the province of Loja", the same one that is being executed in the Plant Micropropagation Laboratory of the Universidad Nacional of Loja. To obtain the plant material for the implantation and induction phase of explants of C. officinalis L., coded seedlings from 5 to 15 cm high were collected from the greenhouse of the study site: Uritusinga. In the explant disinfection phase, 25,00 % sodium hypochlorite (NaClO) was applied; 50,00 % and 75,00 % and 5,00 % hydrogen peroxide (H2O2) for 10,00 % and 15,00 %, for 10 minutes respectively, the disinfected explants were inoculated in solid medium of Murashige y Skoog (MS, 1962) supplemented with vitamins. The disinfection with 50,00 % and 75,00 % NaClO for 10 minutes, was more effective, in the control of explant contamination, by 40,00 %. For the callus induction phase, the explants were grown in solid MS culture medium, supplemented with auxin and cytokinin in different concentrations: 2-4 D in concentrations of 1,00; 2,00 and 3,00 mg L-1 plus kinetine 0,50 mg L-1 respectively. It was observed that the combination of the two growth regulators were effective in obtaining calligraphic structures. Thus, the combination of auxin and cytokinin was the most effective, obtaining 73,30 % callus formation in treatment 7 (3,00 2-4D mg L-1 + 0,50 mg L-1) KIN). Key words: Cinchona officinalis L, desinfection, induction, calluses, cascarilla.